New Liquid Crystalline Elastomeric Films Containing a Smectic Crosslinker: Chemical and Physical Properties - Andraz Resetic; Jerneja Milavec; Alexej Bubnov; Damian Pociecha; Vera Hamplova; Ewa Gorecka; Bostjan Zalar; Valentina Domenici (Crystals, 2023)
Side-chain liquid crystal elastomers (SC-LCEs) have been designed by using a new smectic crosslinker. Two types of monodomain films were prepared based on polysiloxane chains, with a different relative concentration of both crosslinker and mesogenic comonomers. The mesomorphic behavior of the two SC-LCE systems was investigated by differential scanning calorimetry and polarized optical microscopy showing a different mesomorphic behavior: in one case, we obtained a nematic SC-LCE film, in the other case, a Smectic A SC-LCE film. In both systems, the mesophases were stable in a wide temperature range. Moreover, the SC-LCE films possess a relatively high orientation at room temperature. The physical-chemical properties, such as the local orientational ordering, structural organization, and dynamics of SC-LCEs’ constituents were studied by means of static and dynamic 2H NMR experiments, small-angle X-ray, and wide-angle X-ray diffractions. The relevant physical properties, such as the thermo-elastic and thermo-mechanic behaviors, are reported and discussed in view of the practical applications.